Vitamin D in ageing: an investigation into the role of vitamin D in cognitive and physical functioning in coummunity-dwelling older adults - ASPELL, NIAMH (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2018)
With our growing older population, there is an increasing need to identify potentially modifiable characteristics or interventions that are intended to enhance the functioning of older adults who could be described as ageing normally. Vitamin D has been hypothesised to play a role in cognitive and physical function in older adults and this thesis sought to explore vitamin D as a preventative strategy for healthy ageing. We evidenced that year-round vitamin D deficiency (<30nmol/L) was highly prevalent (26.4%) in a large, representative sample of community-dwelling older adults (ELSA)1 with more than half identified as vitamin D deficient (<50nmol/L, 57.3%). We identified that those at most risk of deficiency were of non-white ethnicity, aged 80+, residing in the north of England while the protective effects were noted in supplement users. Subsequently, we conducted the first RCT pilot study2 of vitD3 supplementation (2000IU/day) and pre-specified cognitive and physical outcomes in community-dwelling older adults. We demonstrated the effectiveness and safety of vitamin D3 supplementation on serum 25(OH)D levels with a marked improvement in serum concentrations in the vitD3 group after 6-months and no adverse events were reported. There was no effect of vitD3 supplementation and a comprehensive battery of global and domain-specific cognitive functions, nor an effect in measures of physical function; handgrip strength and TUG3. However, an indication was observed for tasks of memory and attention and physical measures of lower-extremity performance in those with sufficient 25(OH)D status. Furthermore, analysis of the ELSA participants revealed that low vitamin D status (<30nmol/L) was significantly linked with poor lower-extremity physical performance using a validated physical performance battery (SPPB), warranting the use of composite measures of functioning in future multi-model interventions. To conclude, vitamin D deficiency is highly prevalent in community-dwelling older adults. However, findings from a RCT did not support an effect of vitD3 and cognitive and physical function. Observational evidence supports a link between low vitamin D status and poor functional outcomes in healthy older adults. Future interventions should consider testing a combination of modifiable lifestyle factors, in larger, more diverse cohorts of older adults, using comprehensive assessments of muscle function and cognitive performance. 1. English Longitudinal Study of Ageing (n=6004) 2. Randomised double-blind placebo-controlled pilot trial (Clinicaltrials.gov identifier: NCT02804841) 3. Timed-Up-and-Go test (TUG) 4. Short Physical Performance Battery (SPPB)
APPROVED
Keywords: Cognition; Physical function; Serum 25(OH)D; Community-dwelling; Vitamin D; Ageing